2023
DOI: 10.3389/fphys.2023.1220048
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associates with semen inflammation and sperm quality impairment that reverses in the short term after disease recovery

Abstract: Introduction: COVID-19 exerts deleterious effects on the respiratory, cardiovascular, gastrointestinal, and central nervous systems, causing more severe disease in men than in women. However, cumulative reported data about the putative consequences on the male reproductive tract and fertility are controversial. Furthermore, the long-term effects of SARS-CoV-2 infection are still uncertain.Methods: In this study, we prospectively evaluated levels of inflammatory cytokines and leukocytes in semen and sperm quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…We assessed standard sperm quality parameters in patients younger and older than 35 years, 5-7 months after recovery from COVID-19. In many studies, the recovery period for sperm parameters is 1 or 2 cycles of spermatogenesis [7,16,28,29]. This may explain why we did not find statistically significant differences in the studied markers.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We assessed standard sperm quality parameters in patients younger and older than 35 years, 5-7 months after recovery from COVID-19. In many studies, the recovery period for sperm parameters is 1 or 2 cycles of spermatogenesis [7,16,28,29]. This may explain why we did not find statistically significant differences in the studied markers.…”
Section: Discussionmentioning
confidence: 68%
“…According to recent reports, various levels of cytokines are typically found in seminal plasma within normal ranges [30]. However, even 2-3 months after recovering from COVID-19, alterations in the levels of both pro-inflammatory cytokines, such as IL-1β, IL-6, TNFα, and the anti-inflammatory cytokine IL-10, have been observed in semen [11,16]. Additionally, Yu et al have suggested that the cytokine storm in COVID-19 patients is associated with enhanced levels of 13 specific cytokines (including IL-1, IL-6, IL-10, and TNFα), potentially affecting male fertility through damage to testicular cells and impairment of the immune microenvironment [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where there is a relatively large body of evidence, however, is how single and multiple COVID-19 infections can harm male and female fertility (Aksak et al, 2022; Chen et al, 2021; Harb et al, 2022; Hosseini et al, 2023; Martinez et al, 2023; Patel et al, 2021; Saadedine et al, 2023; Wesselink et al, 2022). And this could be one of the reasons for the decline in births in the second half of 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals infected with COVID‐19 often exhibit symptoms such as cephalalgia, rhinorrhea, sneezing, pharyngitis, anosmia, and ageusia. Nevertheless, it is worth noting that a significant proportion of patients, around 80%, may have long‐term complications affecting various bodily systems, such as the neurological, 2 urogenital, 3 and digestive systems 4 diseases over the weeks or months after their recovery. The consequences of COVID‐19 exhibit a range of severity, which may be attributed to substantial variations among individuals.…”
Section: Introductionmentioning
confidence: 99%